The Mellon Chansonnier, reflections of the "Roman de la Rose": The reception by Molinet and Tinctoris, a manuscript for the House of Aragon - Benner, Karen Elizabeth Zacy (University of Ottawa (Canada), 2003)
In this study the Mellon Chansonnier, a collection of predominantly secular Burgundian polyphonic chansons dating from the late 15th century is considered as an intentionally crafted and textually thematic cohesive manuscript. The manuscript of Neapolitan origins was organized and prepared under the auspices of the renowned theorist Johannes Tinctoris for Beatrice of Aragon, daughter of King Ferrante I of Naples at the time of her marriage to King Matthias Corvinus of Hungary. The themes present in the chansons reflect the characters and discourses present in the 13th century poem written by Guillaume de Lorris and Jean de Meun, the Roman de la Rose . The significance of this thematic comparison is heightened by parallels drawn between the literary references to the Roman de la Rose and the court of the House of Aragon. The readings of these secular chansons within a literary and social context are further expanded into moralities. The translation and moralization of the poem by Jean Molinet, a Burgundian court chronicler, musician, and poet sheds light on alternate readings of the courtly love poem. (Abstract shortened by UMI.)
Keywords: Music.